PENGARUH PENGGUNAAN MEDIA TEBAK GAMBAR TERHADAP LITERASI MEMBACA SISWA DI KELAS II UPT SPF SD INPRES BANGKALA III - Satriani; Supardi, R; Amaliyah, Nurhadifah; Alam, Syamsul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low reading literacy ability of elementary school students is influenced by the use of less varied learning media so that students tend to be less active and less motivated in the learning process. This study aims to determine the effect of using picture guessing media on the reading literacy of second-grade students of UPT SPF SD Inpres Bangkala III. The study used a quantitative approach with a pre-experimental research type through a One Group Pretest–Posttest Design. The research sample consisted of 28 second-grade students of class II B who were determined using a purposive sampling technique. Data collection was carried out through tests, observations, and documentation. Data were analyzed using descriptive statistics and inferential statistics with normality tests, homogeneity tests, and Paired Sample t-Tests assisted by SPSS version 22. The results showed that the application of picture guessing media was carried out very well, while student activity was in the good to very good category. The results of the analysis showed an increase in students' reading literacy abilities after participating in learning using picture guessing media. Hypothesis testing through Paired Sample t-Test showed a significance value (Sig. 2-tailed) less than 0.05 so that the alternative hypothesis was accepted. Thus, the use of picture guessing media has a significant effect on increasing reading literacy of class II students at UPT SPF SD Inpres Bangkala III.